Effect of Famotidine and Diclofenac on Theophylline Pharmacokinetics in the Rabbit - Otoom, Sameer; A. Hadidi, Kamal; Irshaid, Yacoub; Battah, Abdel-Kader; F. Hadidi, Hakam (Asian Journal of Chemistry, 2016)
The aim of this investigation is to study drug interaction between theophylline-famotidine and theophylline-diclofenac in New Zealand white male rabbits. The serum concentration-time profile and the pharmacokinetics parameters of theophylline given alone intravenously (10 mg/kg) and following pre-treatment with either oral famotidine (5 mg/kg) or intramuscular diclofenac (5 mg/kg) were calculated. Theophylline serum concentrations in the rabbit were measured by radio-immunoassay and the pharmacokinetics parameters were computed using the computer program PKCALK. There were no statistically significant changes in the area under the plasma concentration-time curve, half life, clearance, volume of distribution or the mean residual time before and after famotidine or diclofenac pre-treatment. It is concluded that famotidine and diclofenac did not alter the pharmacokinetics of theophylline in the rabbits.